Optimal bidding strategy for an aggregator of prosumers in energy and secondary reserve markets. (15th March 2019) - Iria, José; Soares, Filipe; Matos, Manuel
Highlights: Participation of an aggregator of prosumers in energy and secondary reserve markets. Two-stage stochastic optimization bidding model. The uncertainty of the prosumers information is modeled through a set of scenarios. The results suggest cost savings of 40% for both aggregator and prosumers. Abstract: This paper proposes a two-stage stochastic optimization model to support an aggregator of prosumers in the definition of bids for the day-ahead energy and secondary reserve markets. The aggregator optimizes the prosumers' flexibility with the objective of minimizing the net cost of buying and selling energy and secondary reserve in both day-ahead and real-time market stages. The uncertainties of the renewable generation, consumption, outdoor temperature, prosumers' preferences, and house occupancy are modeled through a set of scenarios. For a case study of 1000 prosumers, the results show that the proposed bidding strategy reduces the costs of both aggregator and prosumers by 40% compared to a bidding strategy typically used by retailers.